Aspects of students’ performance interaction in practical application For the subject of methods of teaching art education (Journal of the College of Basic Education, 2025)
The current research aims to reveal the aspects of performative interaction practiced by the art education student in the applications of the teaching methods subject. Therefore, the methodology of its procedures is directed towards the experimental method as it is the most appropriate scientific method to achieve the research goal.The researcher adopted the experimental design for one sample, which is based on two variables, the first represented by the independent variable (performative interaction) and the second represented by the dependent variable represented by (practical application) in the subject of methods of teaching art education. The research community consists of third-year students / Art Education Department for the academic year 2021 / In 2022, the researcher selected a random sample of (19) male and (10) female students from the third grade - Department of Art Education. To extract the results, the researcher used a set of statistical methods.The most important conclusions are: The efficiency of students applying the practical aspect of the Art Education Teaching Methods subject after being guided according to the educational content of the teaching plans. This is due to the sequence of steps for the practical application of this subject.